Spin photovoltaic effect in antiferromagnetic materials: Mechanisms, symmetry constraints, and recent progress - Xiao, Rui-Chun (2023)
Antiferromagnetic (AFM) materials possess unique properties, such as rapid dynamic response, resistance to external magnetic disturbances, and the absence of a stray field. AFM materials are important members in the field of spintronics, and generating the spin current in AFM materials is one of the vital topics for AFM spintronics. The spin photovoltaic effect (SPVE) is the spin counterpart of the bulk photovoltaic effect (BPVE), where the photocurrent is spin-polarized. This effect can generate spin current in a contactless and ultra-fast way. Recently, SPVE has garnered significant interest due to its potential application in AFM spintronics and rich physical content. In this perspective, the mechanism of SPVE, including the relationship between SPVE and BPVE, and symmetry constraints are reviewed. We also provide an overview of recent progress on SPVE in AFM materials. This perspective also offers a viewpoint on this exciting area of research.